Cytotoxic Activity Of Certain Medicinal Plants Extracts Against Sea Monkey: Artemia Salina - Mayilsamy, M.; Geetharamanan, K. (Journal of Medicinal Herbs and Ethnomedicine, 2016)
Cytotoxicity assays are widely used by the pharmaceutical industry to screen compound libraries. ArtemiaÂ populations are found in about 500 natural salt lakes and man-made salterns scattered throughout the tropical, subtropical and temperate climatic zones, along coastlines as well as inland. This general bioassay is not only rapid, it is also reliable. In the present investigation, the leaves of angiosperm plants Andrographis paniculata, Argemone mexicana, and Vitex negundo were extracted with solvents of varying polarity such as hexane, ethyl acetate, acetone and methanol and their yield was calculated. The extracts were tested for hatch inhibition of cysts of Artemia salina and cytotoxic activities against Artemia salina naupilii. The overall values of HI percentage ranged from 85.6 to 100%. Among the different extracts of three plants studied the methanol extract showed more potent cytotoxic activity than other extracts.